A Case Study of the Likes and Dislikes of DNA and RNA in Self‐Assembly. Issue 50 (12th October 2015) - Zuo, Hua; Wu, Siyu; Li, Mo; Li, Yulin; Jiang, Wen; Mao, Chengde
Abstract: Programmed self‐assembly of nucleic acids (DNA and RNA) is an active research area as it promises a general approach for nanoconstruction. Whereas DNA self‐assembly has been extensively studied, RNA self‐assembly lags much behind. One strategy to boost RNA self‐assembly is to adapt the methods of DNA self‐assembly for RNA self‐assembly because of the chemical and structural similarities of DNA and RNA. However, these two types of molecules are still significantly different. To enable the rational design of RNA self‐assembly, a thorough examination of their likes and dislikes in programmed self‐assembly is needed. The current work begins to address this task. It was found that similar, two‐stranded motifs of RNA and DNA lead to similar, but clearly different nanostructures. Abstract : The composition of a nucleic acid nanomotif (RNA or DNA) has a significant influence on its structure. DNA motifs with certain single‐stranded loops and tails yielded triangular prisms (see scheme, left and right) whereas two complementary motifs need to be combined to obtain tetragonal prisms (middle).